TemuAksi: Mobile Application for Connecting Sponsors and Event Organizers - Yafianto, Imanuel Felix; Ardita, Alifia; Hammam, Muhammad Raynar; Amalina, Mirza Nabil Khoirunisa; Mukhlis, Iqbal Ramadhani (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2026)
The development of events such as seminars, competitions, festivals, and social activities continues to increase. However, many event organizers still experience difficulties in finding sponsors and recruiting volunteers who match the needs of their activities. On the other hand, companies or sponsors require an effective platform to discover events that align with their promotional objectives. Meanwhile, individuals who wish to become volunteers often face limited access to information regarding opportunities to participate in various events. These issues cause the process of searching for sponsors and volunteers to become inefficient and poorly organized. This research aims to design and develop a mobile application called TemuAksi as a platform that connects event organizers, sponsors, and volunteers. The method used in this research is the Design Thinking approach, which includes the stages of empathize, define, ideate, prototype, and testing to produce solutions that focus on user needs. The result of this research is the design of the TemuAksi mobile application, which provides features such as event search, sponsorship proposal submission, volunteer registration, and a communication system between users. This application is expected to improve the effectiveness of collaboration between event organizers, sponsors, and the community, while also supporting the creation of digital partnerships aligned with SDG 17: Partnerships for the Goals.